Does corporate governance and political connections influence the potential for financial statement fraud? - Cahyani, Ari Singgar; Arifin, Johan (Jurnal Akuntansi dan Auditing Indonesia, 2024)
The aim of this research is to analyze the influence of corporate governance and political connections on the potential for financial statement fraud in extractive industry companies listed on the IDX for the 2018-2023 period. The sampling was performed using the purposive sampling method. A logistic regression analysis was performed. The results of this research indicate that corporate governance proxied by the frequency of audit committee meetings, managerial ownership, and related party transactions has a positive effect on the potential for financial statement fraud, while the size of the board of directors has no effect. Political connections proxied by government ownership and politically connected boards negatively affect the potential for financial statement fraud. The addition of control variables, namely firm growth, has a positive effect on the potential for financial statement fraud, whereas firm size has no effect.